20 - Th Role of Faith Healing in an HIV High-Risk Area: A Case Study of Balokole Churches in Masaka District, Uganda: Stella Nyanzi - Stella Nyanzi, (CODESRIA Bulletin, 2003)
Diverse modes of health care — western bio-medicine, African traditional therapies, herbalism, Eastern mysticism and alternative therapies such as yoga and ayurvedic medicine, faith healing based on psycho-spiritual models, and many others — co-exist in most African countries (Last 1990, Turner 1968). Medical anthropologists (Kleinman 1980, Helman 1994) have suggested that three basic sectors of health-care can be identified: the popular sector, the folk sector and the professional sector. These sectors overlap and interact, but each sector has its own ways of explaining and treating illness, defining who is the healer and who is the patient and specifying how the healer and patient interact in their therapeutic encounter. Up to now research on health care in Africa has focused mainly on the folk and professional sectors. Yet the popular sector is very dynamic and is constantly evolving in response to contemporary social-cultural phenomena. This paper examines the role of contemporary faith healing in an HIV high-risk area. It is based on field research in Masaka District of southwestern Uganda on modern faith healing churches whose ideology emphasises supernatural, ‘miracle’ healing. Several studies (Rwomushana 2000, Asiimwe-Okorir et.al 1997, Mulder et al. 1995) have attributed Uganda’s success in fighting HIV/Aids to a rigorous multi-sectoral strategy combining holistic health care services with health education, information and communication directed at the rural and urban masses. Under the much praised leadership of the president of Uganda, government departments, public enterprises, non-governmental organisations, community-based organisatoins, multi-national companies and faith-based institutions have all joined hands to combat the epidemic with from as high as 38 percent to less than 7 percent. This paper cuses on the role of one sector in this multi-sectoral partnership, faith healing and miracle churches..